Pengaruh Pelayanan dan Nisbah Bagi Hasil terhadap Minat Menabung Nasabah pada Bank Sumut Syariah Panyabungan - Beni Sandra; Siti Kholijah; Erpiana Siregar (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The aim is to determine the significant influence of Service and Profit Sharing Ratio on Customer Saving Interest at Bank SUMUT KCPSy Panyabungan. This research uses a quantitative description method. Sampling was taken using a simple random sampling technique, by distributing questionnaires directly to 98 respondents. With the help of SPSS version 25. The research results are based on SPSS calculations that service influences customers' interest in saving. This is proven by the calculated t value being greater than the t table, namely: (2,329 > 1.895) with a significant value of 0.022 < 0.05, and the profit sharing ratio influences customers' interest in saving. This is proven by the calculated t value being greater than the t table, namely: (2.258 > 1.895) with a significance value of 0.026 < 0.05, then it can be concluded that the Profit Sharing Ratio (X2) variable has a positive and significant effect on the customer's interest in saving variable. (Y). This is proven by the calculated F value of 5.654 > 3.092, a significant value of 0.005 < 0.05.